(untitled) (Bioscience Journal, 2020)
To identify the influences of the professional training process for action in the Family Health Strategy (FHS) related to the health of the elderly man. Exploratory descriptive research, carried out with 20 professionals, from a Brazilian Northeast municipality from October to December 2014. The data collection was performed through a questionnaire, following the statements were processed in the software IRaMuTeQ, analyzed by the Descending Hierarchical Classification. Three classes emerged: Influences of the professional training process on elderly health care; Health care for the elderly; Actions developed in the family health strategy in the implementation of the national policy of comprehensive health care for the elderly. The findings suggest improved knowledge, lack of resources and medical specialties, evidenced the complexity of the actions developed by health professionals.